Fuel Usage of Selected Road Vehicles Operating on Common and Alternative Fuels in Iceland 2009-2010. Incorporating Driving Behavior and Vehicle Characteristics - Elísabet Björney Lárusdóttir 1978- (2010)
This study examines variables that affect fuel consumption of road vehicles, such as driving behavior, vehicle characteristics, and the difference between fuels used. The objectives were to gather data from a selection of road vehicles that were fuelled with alternative fuels (gasoline, diesel, methane, hydrogen) in Iceland and to identify the difference in vehicle efficiency as a measure of the vehicles’ fuel consumption. The goal is to provide recommendations to decrease the overall emission from the transport sector in Iceland. Data was collected with SAGAsystemTM GPS monitoring devices and fuel cards. A linear regression was performed on the amount of gasoline for each refill as a function of observed variables. The results show that acceleration has a statistically significant effect on the vehicles’ fuel consumption. In order to minimize fuel consumption, speed must be increased with a moderate acceleration and average speed should be as steady as possible. Hydrogen and Methane provided the overall best results in fuel consumption when compared with the other types of fuels, and with all other factors kept fixed. The Toyota Prius hybrid vehicles use regenerative braking and the frequency of severe braking instances causes a statistically significant less energy consumption for these vehicles. It is recommended that for future research on energy consumption of vehicles, that a fuel monitor computer be installed in each vehicle in order to gain better data for analysis within each refill period. These results should be taken into consideration when developing policy or plans to decrease the total emissions from the road transport sector in Iceland. Íslensk Nýorka, Rannís